Nari Prescribes Stereotype Gender Roles - Sharma, Bimala (Janapriya Journal of Interdisciplinary Studies, 2020)
This research article tries to focus on how Sarvottam Nari one of the print media of Kantipur Publications prescribes stereotypical gender roles to female. Kantipur Publications’ Sarvottam Nari dated Mangsir 2076 (Nov-December 2019) is chosen to study how it prescribes gender roles. A qualitative research methodology is employed to scrutinize the text. Though Kantipur Publications, in its Website ekantipur.com, asserts that “the company firmly believes in the people’s right to right information (Homepage) it is not disseminating the right information instead it allocates stereotype gender roles. It is restricting women to precise territories such as homemaking, child-caring, food preparing, body decorating, entertaining herself and her male counterpart. By allocating traditional roles to women, Nari, cannot transmit the right information and work as an instrument of the social transformation instead it works to disseminate the male mindset/ideology. Findings of the study prove that Nari (Nov-December 2019) has proposed, transmitted and reinforced patriarchal ideologies which restrict women in the four walls of house and prescribe the traditional gender roles